2021
DOI: 10.1002/app.52038
|View full text |Cite
|
Sign up to set email alerts
|

Interlaminar fracture and crack‐healing capability of carbon fiber/epoxy composites toughened with 3D‐printed poly‐ε‐caprolactone grid structures

Abstract: In this study, carbon fiber (CF)/epoxy (EP) composites are toughened with 3Dprinted poly-ε-caprolactone (PCL) grid structures which are produced by fused deposition modeling at three different areal weight densities and place between dry plain-weave carbon fabrics prior to resin infusion. Three-point bending, Mode-I fracture toughness, interlaminar shear strength (ILSS), and Charpy impact tests are carried out on the prepared composite specimens. The results show that the PCL interlayers can enhance Mode-I fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…No matter what the self-healing approach is, apart from the main challenge of maintaining a high volume fraction of the reinforcing fibers and adequate mechanical properties for the healable composite, another critical point is represented by the difficulty in finding a common healing efficiency testing method, shared among all the scientific community. The most frequently adopted test methods are either nondestructive analysis, such as C-scans, or are based on mechanical tests such as Mode I double cantilever beam (DCB), tapered double cantilever beam (TDCB), Mode II end-notched flexure (ENF) testing, compression after impact (CAI), bending after indentation, fatigue, and tensile, and bending testing (Tesoro and Sastri, 1990;Meure et al, 2009;Park et al, 2009;Williams et al, 2009;Patrick et al, 2014;Luterbacher et al, 2015;Manfredi et al, 2015;Hia et al, 2016;Lucas et al, 2016;Sordo and Michaud, 2016;Zhang and Li, 2016;Michaud, 2017a, 2017b;Cohades et al, 2018;Hostettler et al, 2019;Kanu et al, 2019;Beylergil, 2021;Kamble et al, 2021;Jony et al, 2022;Kamble et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No matter what the self-healing approach is, apart from the main challenge of maintaining a high volume fraction of the reinforcing fibers and adequate mechanical properties for the healable composite, another critical point is represented by the difficulty in finding a common healing efficiency testing method, shared among all the scientific community. The most frequently adopted test methods are either nondestructive analysis, such as C-scans, or are based on mechanical tests such as Mode I double cantilever beam (DCB), tapered double cantilever beam (TDCB), Mode II end-notched flexure (ENF) testing, compression after impact (CAI), bending after indentation, fatigue, and tensile, and bending testing (Tesoro and Sastri, 1990;Meure et al, 2009;Park et al, 2009;Williams et al, 2009;Patrick et al, 2014;Luterbacher et al, 2015;Manfredi et al, 2015;Hia et al, 2016;Lucas et al, 2016;Sordo and Michaud, 2016;Zhang and Li, 2016;Michaud, 2017a, 2017b;Cohades et al, 2018;Hostettler et al, 2019;Kanu et al, 2019;Beylergil, 2021;Kamble et al, 2021;Jony et al, 2022;Kamble et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In Mode I DCB and Mode II end-notched flexure (ENF) testing, the composite samples undergo loading-unloading cycles that allow to record force-displacement curves and crack advancement. Healing efficiency can then be defined on stiffness-based or interlaminar fracture toughness calculations (Cohades and Michaud, 2017b) (Meure et al, 2009;Patrick et al, 2014;Cohades and Michaud, 2017b;Beylergil, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the reference specimens, there are only a few load drops since the crack propagates suddenly in these composites. [ 43 ] The crack extends more than 10 mm in one jump. It can be concluded that the crack propagation in neat nano‐CaCO 3 reinforced composites was unstable.…”
Section: Resultsmentioning
confidence: 99%
“…Szebényi et al 55 utilized 3D-printed polycaprolactone (PCL) interlayers with various geometries on CF/EP prepregs, significantly increasing the composites' ductility. Beylergil 56 also demonstrated a nearly sevenfold increase in Mode-I fracture toughness of CF/EP composites using 3D-printed PCL interlayers. FDM offers opportunities in interface engineering with various polymers, including PA, which shows great promise for enhancing the mechanical properties of CF/EP composites.…”
Section: Introductionmentioning
confidence: 89%